The Size of the Household of Šiauliai Parish Residents in the First Half of the 19th Century (According to the Data of the Visitations) - Giedrimas, Laurynas (Acta humanitarica academiae Saulensis, 2023)
The article aims to reveal the possibilities of the data contained in the parish visitations in determining the average household size of the residents of Šiauliai parish. Firstly, the data on visitations allows us to learn about the number of residents who came to catholic confession and those who did not come to catholic confession. Secondly, the source allows us to learn about the number of households in all parish settlements. The data is important for calculating the number of residents in the settlements and in the whole parish. The data on the number of residents allows us to calculate the size of the households in separate settlements and in the whole parish. Moreover, this data can be used for the reconstruction of parish geographical territory. On the other hand, the data on parish visitations can be incorrect as usually statistical information was rewritten from the earlier sources. Considering Šiauliai catholic parish visitations, it should be noted that later visitations were rewritten from the visitations of the year 1820, thus this research only deals with the situation of the year 1820. The analysis revealed that the geographical territory of Šiauliai parish has not significantly changed since the middle of the 17th century. Also, those settlements that were the largest in terms of population in the middle of the 17th century, remained the largest in the first half of the 19th century. After calculating the ratio of those who went to confession and those who did not go, it was found that in the visitations of Šiauliai parish, only the number of Catholics was given, and in some settlements far from the center of the parish, there was a high number of those who did not go to confessions, most likely it indicates pastoral problems, and not the population of other denominations. On average, 9.7 people lived in one household in Šiauliai parish, 7.98 lived in Šiauliai city, 14.5 lived in Kužiai town, and 11.35 lived in Meškuičiai town. After comparing the results of the research with the data of other cities and towns, it can be said that larger cities were characterized by smaller households, while small towns were characterized by larger households. Meanwhile, it is not easy to compare the obtained research results with the household data of the Central and Eastern European population, because the research results are highly dependent on the concept of the household. Nevertheless, it can be said that the average household size of Šiauliai parish was close to the household size of the residents of Nereta (Latvia).